PENGEMBANGAN DAYA TARIK WISATA DESA PUNGUT MUDIK, KECAMATAN AIR HANGAT TIMUR - Yolla Ramadani; Anggia Ayu Lestari; Alfikry Fitrah Aidil; Fami Afrilianto Azhari (Universitas Majalengka, 2023)
Tourism is one of the supporters of national economic growth, so it is very important for villages to be able to develop tourism potential in their area. The potential of a good tourist village will be the main attraction of a tour in encouraging tourists to visit the tour. In developing tourism potential, of course, requires the participation of all elements, both from the community and also from the government. Pungut Mudik Village has the potential for several tourism objects that can be developed so as to improve the community's economy. However, the lack of public knowledge about the natural potential they have so that this tourist attraction has not been developed until now. The purpose of this community service activity is to provide socialization and assistance for the people of Pungut Mudik Village about developing the potential of their village so that later the community will have knowledge about tourist villages that can improve the community's economy. Methods of implementation through surveys, interviews, socialization and counseling as well as facilitation. Pariwisata merupakan salah satu penyokong pertumbuhan ekonomi nasional, sehingga sangat penting bagi desa untuk bisa mengembangkan potensi wisata yang ada didaerahnya. Potensi desa wisata yang baik akan menjadi daya tarik sebuah wisata dalam mendorong wisatawan untuk mengunjungi wisata tersebut. Dalam pengembangan potensi wisata tentunya membutuhkan partisipasi dari semua elemen, baik dari masyarakat dan juga dari pihak pemerintahan. Desa Pungut Mudik memiliki potensi beberapa objek wisata yang dapat dikembangkan sehingga dapat meningkatkan perekonomian masyarakat. Akan tetapi kurangnya pengetahuan masyarakat tentang potensi alam yang mereka miliki sehingga daya tarik wisata rtersebut belum dikebangkan sampai saat ini. Tujuan kegiatan pengabdian kepada masyarakat ini adalah memberikan sosialisasi dan pendampingan bagi masyarakat Desa Pungut Mudik tentang pengembangan potensi desa yang mereka miliki sehingga nantinya masyarakat memiliki pengetahuan tentang desa wisata yang dapat eningkatkan perekonomian masyarakat. Metode pelaksanaan melalui survei, wawancara, sosialisasi dan penyuluhan serta fasilitasi.